Association between chronic diseases and depression in the middle-aged and older adult Chinese population—a seven-year follow-up study based on CHARLS - Zhou, Pengfei; Wang, Shuai; Yan, Ya; Lu, Qiang; Pei, Jiaxing; Guo, Wang; Yang, Xiaoguang; Li, Yunming (Frontiers in Public Health, 2023)
Background: With the aging of the Chinese population, the prevalence of depression and chronic diseases is continually growing among the middle-aged and elderly people, but there are few studies on the relationship between the depression and chronic diseases in the middle-aged and elderly populations. The aim of this study was to investigate the relationship between the depression and chronic diseases in the Chinese middle-aged and elderly population. Methods: Data from the China Health and Retirement Longitudinal Study (CHARLS) 2011-2018 longitudinal survey, a 7-years follow-up of 7163 participants over 45 years old, with no depression at baseline (2011). The chronic disease status in our study was based on self-report of the participants, and the depression was defined by the 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10). The relationship between baseline chronic disease and depression was assessed by the Kaplan-Meier method and Cox proportional hazards regression models. Results: After 7-years follow-up, 41.2% (2951/7163, 95% CI:40.1%, 42.3%) of the participants reported depression. The analysis showed that participants with chronic diseases at baseline had a higher risk of depression and that such risk increased significantly with the number of chronic diseases suffered (1 chronic disease: HR=1.205; 2 chronic diseases: HR=1.341; 3 and more chronic diseases: HR=1.432). Kidney disease (HR=1.289), stomach or other digestive diseases (HR=1.129), and arthritis or rheumatism (HR=1.263) all significantly increased the risk of depression in middle-aged and elderly Chinese. Conclusions: The present study found that suffering from different degrees of chronic diseases increased the risk of depression in the middle-aged and elderly people, and these findings may benefit for preventing depression and improving the quality of mental health in this group.